En busca del espectáculo prehispánico nahua en fiestas y representaciones teatrales coloniales - Agnieszka Brylak (Ksiegarnia Akademicka Publishing, 2021)
The aim of this paper is to present civil and religious festivals, as well as theatrical representations, performed in the sixteenth‑century New Spain, as examples of the convergence of elements introduced by the Spaniards and those already existing in the indigenous culture. Taking as a starting point a schematic presentation of such activities as dances, song performances, jugglers’ shows, mock battles and evangelization theater, our objective is to signal that due to the presence of certain pre‑Hispanic patrons for all these endeavors it is risky to qualify the indigenous contribution as superficial and limit it to the audiovisual elements. The issue is much more complex and the adoption of the native perspective, apart from that of the Spaniards, may reveal the profundity of the convergence of features proper to the Old and New World and help to unveil the perception and reception of the sixteenth‑century Mexican performances by its native inhabitants.